Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional dan Kecerdasan Spiritual Terhadap Sikap Etis Mahasiswa Akuntansi : Studi Empiris Pada Mahasiswa Prodi Akuntansi Universitas Nusa Nipa - Ambrosiana Srivici Eken; Pipiet Niken Aurelia; Fransiscus De Romario (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This research aims to investigate the impact of intellectual intelligence, emotional intelligence and spiritual intelligence on the ethical attitudes of accounting students at Nusa Nipa University using quantitative methods. The research will focus on students enrolled in the accounting program from the 2020-2022 intake, with a total of 426 participants. The sample for this research comprised 81 accounting students who were the the subjects of the research. The findings indicate that intellectual intelligence(x1) and spiritual intelligence (x2) positively influence the ethical attitudes (y) of accounting Students At Nusa Nipa Univercity. However, emotional intelligence (x2) does not have an impact on the ethical attitudes (y) of accounting students at Nusa Nipa Univercity.